ПРОФИЛАКТИКА СОСТОЯНИЯ ТРЕВОЖНОСТИ У МЛАДШИХ ШКОЛЬНИКОВ - Лариса МОСКАЛЮК (Moldova State University, 2020)
Мы изучали и исследовали наличие страхов и проявление тревожности у детей младшего школьного возраста, старались обосновать причины появления страхов у детей, рассматривали динамику развития тревожности и зависимость от взаимоотношений с родителями, воспитателями. Изучаемая в работе проблема представляет, на наш взгляд, интерес для психологов, воспитателей, психиатров и родителей, так как тревожность и cтрахи оказывают негативное влияние не только на учебную деятельность детей младшего школьного возраста, на взаимоотношения, но и на здоровье в целом. Необходимо продолжать исследования, с упором на профилактическую деятельность.   PROPHYLAXIS STATE ANXIETY THE SMALL SCHOOL This scientific work is dedicated to the great problems of children's fear and state of anxiety. I studied and investigated the present fear and the children's display of the state of anxiety and I examined the influence of factors to the state of their anxiety. To my mind investigating this work is a very important problem because the state of anxiety and fear are very negative not only for children's learning knowledge but to their whole state of health. So the general conclusion to the research results may produce a great interest not only for parents but for psychologist, teachers, doctors, psychiatrist and neuropathologists, because these are necessary arguments and prophylaxes for the children's state of anxiety and also for the formation of the harmony's personal development to their social, harmonically development and choice of their life. To my opinion it is very important to continue the beginning which is very persistent with great emphasize to the prophylactic activity.